KINETICS OF Pb AND Zn LEACHING FROM ZINC PLANT RESIDUE BY SODIUM HYDROXIDE - Erdem, M.; Yurten, M. (Technical Faculty, Bor-Serbia, 2015)
In the hydrometallurgical zinc production processes, important amount of hazardous solid extraction residue containing unextractable Zn and Pb is generated. Due to increasing demand of metals and the depletion of high grade natural resources, these types of wastes are gaining great importance in the metallurgical industries. In this study, selective leaching and leaching kinetics of Pb and Zn from zinc extraction residue were investigated. For this purpose; the effects of NaOH concentration, contact time, stirring speed and temperature on the Pb and Zn recovery from the residue were studied. The shrinking core model was applied to the results of the experiments. Leaching results showed that 85.55% Pb and 21.3 % Zn could be leached under the optimized conditions. The leaching of Pb and Zn were found to fit well to shrinking core model with ash layer diffusion control. Activation energy values for Pb and Zn leaching were calculated to be 13.645 and 22.59 kJ/mol, respectively.
Keywords: Zinc extraction residue; Recovery; Leaching; Shrinking core model